Research on dynamic uplift of contact wires in high-speed railway - TANG Yang (机车电传动)
This paper aims to study the dynamic behaviors of the pantograph-catenary system for high-speed railway lines, focusing on the overall uplift data of contact wires. To achieve this, models of overhead contact systems (OCS) were established for four typical high-speed railway systems, along with three-degree-of-freedom models with reduction parameters for three types of high-speed pantographs. Moreover, the penalty function method was introduced to simulate pantograph-catenary interactions, leading to the establishment of a pantograph-catenary coupling model that was then utilized to simulate uplift changes of contact wire steady arms under different operating speeds and directions. Subsequently, an intelligent locating point recognition and classification method was proposed, based on the random forest algorithm. By using the inflection points of contact wire staggers as locating points, and leveraging existing detection data for the geometric parameters of the overhead contact systems, the voting results from the random forest algorithm were considered standards for determining the final locating points. Furthermore, a classification model was established to optimize the locating point data. After preprocessing the data obtained from the dynamic and static measurements of contact wire uplift, optimizing the locating points, and performing data spatial synchronization, continuous contact wire uplifts were ultimately generated. The research results indicate that the maximum uplift of the four typical steady arms increases with the increase in train operating speeds within the range of 170 km/h to 350 km/h. Under the conditions of 300 km/h and pantograph opening operation, the dynamic maximum uplift of steady arms for SSS400+ pantographs is smaller than that for the Faiveley CX-018 and DSA380 pantographs. The maximum uplifts ranged from 61.17 mm to 81.44 mm. Under specific OCS parameters, the average uplift of the contact wires during operation in the pantograph closing direction is higher than that during operation in the opening direction.